Numero de cromosomas de Alnus acuminata H.B.K. - Coba de Gutierrez, B.=700 1 Alvarado de Coral, C.
(En, Es)
Ilus., 8 ref.
Keywords: ALNUS ACUMINATA; CROMOSOMAS; NUMERO DE CROMOSOMAS; COLOMBIA; AGRONOMIA COLOMBIANA